Chikanobu and Yoshitoshi Woodblock Prints : Claremont Colleges Digital Library - Claremont College; Scripps College (2007)
[Dt.:] Bilddatenbank der Sammlung japanischer Drucke des Scripps College mit über 500 Werken der Farbholzschnitt-Meister Chikanobu (1838-1912) und Yoshitoshi (1839-1892). - [Engl.:] Online database providing the Scripps College Collection of Japanese Prints with more than 500 works by the artists Chikanobu (1838-1912) and Yoshitoshi (1839-1892).